2009
DOI: 10.1074/jbc.m109.048405
|View full text |Cite
|
Sign up to set email alerts
|

Magnitude of a Conformational Change in the Glycine Receptor β1-β2 Loop Is Correlated with Agonist Efficacy

Abstract: The efficacy of agonists at Cys-loop ion channel receptors is determined by the rate they isomerize receptors to a pre-open flip state. Once the flip state is reached, the shut-open reaction is similar for low and high efficacy agonists. The present study sought to identify a conformational change associated with the closed-flip transition in the ␣1-glycine receptor. We employed voltage-clamp fluorometry to compare ligand-binding domain conformational changes induced by the following agonists, listed from high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
41
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(48 citation statements)
references
References 37 publications
(58 reference statements)
6
41
1
Order By: Relevance
“…It is noteworthy, therefore, that substitutions of Phe207 in loop C had severe effects on ␤-alanine-and taurine-induced currents (taurine Ͼ ␤-alanine) but little effect on glycine-induced currents. Taken together, these results suggest that glycine, ␤-alanine, and taurine may each induce distinct conformational changes in and around the GlyR binding site (taurine Ͻ ␤-alanine Ͻ glycine), an idea that is also supported by a recent study using fluorescent reporter groups (Pless and Lynch, 2009).…”
supporting
confidence: 64%
“…It is noteworthy, therefore, that substitutions of Phe207 in loop C had severe effects on ␤-alanine-and taurine-induced currents (taurine Ͼ ␤-alanine) but little effect on glycine-induced currents. Taken together, these results suggest that glycine, ␤-alanine, and taurine may each induce distinct conformational changes in and around the GlyR binding site (taurine Ͻ ␤-alanine Ͻ glycine), an idea that is also supported by a recent study using fluorescent reporter groups (Pless and Lynch, 2009).…”
supporting
confidence: 64%
“…The important role of loop C derives from a large body of work using x-ray crystallography (11,(35)(36)(37), molecular dynamics simulation (38 -40), site-directed mutagenesis (41)(42)(43)(44), and electrophysiology (45,46). The data from these studies demonstrates that loop C is flexible in the non-liganded form (22,37) and adopts distinct conformations upon agonist or antagonist binding.…”
Section: Discussionmentioning
confidence: 90%
“…Based on the capability of the WT homomeric GluClα (GluClαWT) receptor to respond to Glu only following exposure to IVM, it was suggested that IVM binding induces a conformational change that enables coupling of Glu binding at α/α intersubunit interfaces to the opening of the ion-channel gate (14,23). To explore this suggestion further, we used a strategy of microchimerism that is based on previous studies showing that in various Cys-loop receptors, the β1β2, Cys, and β8β9 loops of the LigBD interact with the M2-M3 loop of the pore domain to couple neurotransmitter binding to channel gating (23,(35)(36)(37)(38)(39)(40)(41)(42)(43)(44) (e.g., Fig. 1 A and C).…”
Section: Resultsmentioning
confidence: 99%
“…In various Cys-loop receptors, the β1β2, Cys, and β8β9 loops were shown to play a key role in transducing the agonist-binding energy into ion-channel gating force (35)(36)(37)(38)(39)(40)(41)(42)(43)(44). Here, we first demonstrated that although the homomeric GluClαR is not responsive to Glu, the β1β2, Cys, and β8β9 loops of the GluClα subunit are fully capable of coupling Glu binding to channel gating in a heteromeric GluClα/β microchimera that has the sequences of the α-subunit loops.…”
Section: Discussionmentioning
confidence: 99%